Status Hara Tanaman Lada Bangka Belitung - Daras, Usman; Tjahjana, Bambang Eka; Herwan, Herwan (Pusat Penelitian dan Pengembangan Perkebunan, 2012)
Ada indikasi rendahnya produktivitas lada di Bangka Belitung (Babel) disebabkan karena petani tidak mampu merawat tanaman secara baik. Dalam merawat tanaman, petani juga melakukan pemupukan meskipun dosis yang diberikan mungkin lebih rendah dari yang dibutuhkan, bahkan unsur pupuk tertentu lain belum pernah diberikan sama sekali. Indikasi ke arah itu diperlihatkan oleh sering dijumpainya tanaman lada yang memperlihatkan gejala defisiensi hara. Untuk itu dilakukan penelitian dalam bentuk survei tanaman lada petani di Kabupaten Bangka, Bangka Tengah dan Bangka Selatan. Setiap kebun lada contoh terpilih, diamati kondisi umum pertumbuhan dan perkiraan tingkat produktivitasnya dengan mewancarai sejumlah petani lada, serta diambil beberapa contoh daun lada dan tanahnya secara komposit untuk dianalisis kandungan haranya di laboratorium. Hasil penelitian menunjukkan kondisi kebun lada petani memperlihatkan pertumbuhan dan hasil lada yang beragam. Kandungan hara N daun sebagian besar masuk kategori sedang (1,65-2,79% N), bahkan tinggi (> 2,79% N). Hara P pada kisaran 0,10â0,18%, sehingga masuk kategori cukup, meskipun sebagian besar nilainya mendekati batas bawah (0,10% P). Sebagian besar kebun lada (68%) memiliki kandungan K daun rendah (< 1,78% K), bahkan mendekati batas bawah (kritis), 0,33% K. Kandungan Ca pada kisaran 0,33-0,54% (rendah), jauh dari kandungan optimal 1,42-3,33% Ca. Sedangkan status Mg bervariasi dari 0,10% (terendah) sampai 0,46% (tertinggi). Pada kebun-kebun lada dengan kandungan Mg daun berkisar 0,10-0,28% memperlihatkan gejala defisiensi. Nutrient status of black pepper grown in Bangka BelitungABTRACT There are greatly various growth performances of black pepper grown in Bangka Belitung. Among them may be classified into the worse ones or low in achieving of yields due to unability of farmers in maintenance of the crops adequately. To increase yields of the crop, they use fertilizers eventhough the kind and amount of nutrients added may be unappropriate manner or never at all. Nutrient disorders in plant may appear in many ways such as reduced growth, off-colored leaves, abnormally shaped leaves and stems and and a breakdown of certain parts of the plant.Â If deficiency of a certain nurient becomes more severe, visual symptoms may spread over the whole plant leaves, may become more chlorotic or bleached in appearance, and death of plant parts. A field survey was carried out on black peppers grown at Bangka, particularly districts of Bangka, Central Bangka and South Bangka in 2010. Parameters observed were quality of growth, productivity, cultural practices applied, and nutrient content of sampled leaves and soils on which the crops are planted. Lacking of a nutrient supply is some extent easely to be identified from specific symptoms of growth, but some others not or hard because it might be not single factor. Leaf and soil analysis are therefore needed to confirm nutrient status to support the growth. Results show that there were strong evident that status of macro nutrients like N and P are likely not to be serious constraints in growing of the crop. On the other hands, those of K, Ca and Mg are under suboptimal conditions of black pepper. Content of K leave ranged of 0.51 to 1.99% being mostly less than those of the need for optimal growth of black pepper 1.78-2.84% K. The others like Ca and Mg in leaves are also low ranging of 0.33 to 0.54% (low), and 0.10% (deficient) to 0.46% (optimum), respectively. Of the leaves having Mg content ranging from 0.10 to 0.28% reveal chlorotic, a type of deficiency symptom characterized by yellowing localized over individual leaves or isolated between some leaf veins (interveinal chlorosis).